Scholar-spy: the worlds of Professor Sir Peter Russell - Taylor, Bruce (Spanish, Portuguese and Latin American studies in the Humanities, 2024)
Professor Sir Peter Russell (1913–2006) was one of the great British scholars of the twentieth century. Russell, who held the King Alfonso XIII chair of Spanish Studies at Oxford from 1953 to 1981, belongs to those who not only moved with equal facility between history and literature, but made lasting contributions to each as scholar, teacher and mentor, not least to Javier Marías who wrote him into a succession of novels including his magnum opus, Your Face Tomorrow. Russell was also a key figure in the development of Hispanic Studies in Britain and, as shown in this volume, the last to have a conspectus on its evolution both cultural and administrative from the 1930s to the 21st century. To all these endeavours he brought an intensely human and logical approach, the product not only of a massive intellect but of a wealth of personal experience which made him more than a scholar and a man of letters. Russell’s service to his country both before and during the Second World War stands comparison with his academic career. Recruited into secret intelligence in the late 1930s, Russell was sent to Spain during the Civil War where he was unmasked as a spy and barely escaped with his life. Drawing on an array of sources private and public, this biography goes on to uncover his service in wartime intelligence which involved him in the effort to usher the Duke and Duchess of Windsor out of Lisbon in 1940 and as an MI5 counter-espionage officer in the Caribbean, West Africa and Southeast Asia. At the epicentre of this volume, as of Russell’s being, is his swirling mental world, one reconstructed from the detailed and often harrowing revelations found among his papers after his death. This material, of indisputable richness, itself represents an absorbing case study in mental illness and its evolution and treatment on Freudian principles in mid-century. The result is a fully documented, deeply researched and compelling picture of a fascinating figure, his relationships, his writings and his years as professor and servant of the state, one that aims to reach beyond academic biography while asking pertinent questions as to the motivations and impulses that attend every scholarly enterprise and the mind and experiences underpinning it.